Serological Evidence of Orthopoxvirus Circulation Among Equids, Southeast Brazil - Borges, Iara A.; Reynolds, Mary G.; McCollum, Andrea M.; Figueiredo, Poliana O.; Ambrosio, Lara L. D.; Vieira, Flavia N.; Costa, Galileu B.; Matos, Ana C. D.; de Andrade Almeida, Valeria M.; Ferreira, Paulo C. P.; Lobato, Zélia I. P.; dos Reis, Jenner K. P.; et al. (Frontiers in Microbiology, 2018)
Since 1999 Vaccinia virus (VACV) outbreaks involving bovines and humans have been reported in Brazil; this zoonosis is known as Bovine Vaccinia and is mainly an occupational disease of milkers. It was only in 2008 (and then again in 2011 and 2014) however, that VACV was found causing natural infections in Brazilian equids. These reports involved only equids, no infected humans or bovines were identified, and the sources of infections remain unknown up to date. The peculiarities of Equine Vaccinia outbreaks (e.g. absence of human infection), the frequently shared environments and fomites by equids and bovines in Brazilian farms and the remaining gaps in Bovine Vaccinia epidemiology incited a question over OPV serological status of equids in Brazil. For this report, sera from 621 equids - representing different species, ages, sexes and locations of origin within Minas Gerais State, southeast Brazil - were examined for the presence of anti-Orthopoxvirus (OPV) antibodies. Only 74 of these were sampled during an Equine Vaccinia outbreak, meaning some of these specific animals presented typical lesions of OPV infections. The majority of sera however, were sampled from animals without typical signs of OPV infection and during the absence of reported Bovine or Equine Vaccinia outbreaks. Results suggest the circulation of VACV among equids of southeast Brazil even prior to the time of the first VACV outbreak in 2008. There is a correlation of OPVs outbreaks among bovines and equids although many gaps remain to our understanding of its nature. The data obtained may even be carefully associated to recent discussion over OPVs history. Moreover, data is available to improve the knowledge and instigate new researches regarding OPVs circulation in Brazil and worldwide.